Practicality Test Experimental Device of Twisting Modulus As a Medium of Learning Physics - Puspita, Amelia Dwi; Islami, Nur; Yennita, Yennita; Ma’ruf, Zuhdi (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to determine the practicality of a twisting modulus of elasticity experimental device along with student worksheets as a medium of learning physics. The method used as a Research and Development (R & D) with Borg and Galls development model at the stage of preliminary test called a test of practicality. Descriptive analysis of the data obtained by filling the questionnaire score an average yield of every aspect the practicality of using a Likert scale ratings. The results showed that the assessment teachersof experimental device about the shear modulus obtained 3.67 is very high category and 3,77 is high by student. The Results of research on student worksheet as an experimental using obtained 3.77 and 3.30 with very high category by teachers and students. So it can be concluded that the experimental device and student worksheet is practical as a medium of learning physics